PENGARUH PERGANTIAN AUDITOR, UKURAN PERUSAHAAN, LABA RUGI DAN JENIS PERUSAHAAN PADA AUDIT REPORT LAG - Megayanti, Putu; Budiartha, I Ketut (E-Jurnal Akuntansi, 2016)
Financial reporting is a mechanism to deliver information about the resources of the company, which includes the measurement of economic and qualitative resource management through operational performance management. The purpose of this study was to determine the effect of the change of auditors, company size, income and type of company to the audit report lag. This research was conducted on all companies listed on the Indonesian Stock Exchange in 2013 and 2014. The sampling method using purposive sampling technique, with a total sample of 322 companies. Methods of data collection using the method of documentation. The analysis technique used is multiple linear regression. Based on the analysis found that the size of the company, income and type of company negatively affect audit report lag.subsitution auditor does not affect the audit report lag.
Keywords: Audit Report Lag, Substitution Auditors,Company Size, Income, Type of Company